Cytological and enzymological characterization of adult human adipocyte precursors in culture. - Van, R L (1976)
Cell strains were derived from the stromal-vascular fraction of human omental adipose tissue and grown in culture. Since the purpose of this study was to isolate adipocyte precursors from adults, the cells were obtained from nonobese patients 40-60 yr of age. After treatment of adipose tissue with collagenase, mature adipocytes were separated from stromal-vascular fraction cells, and cell strains of the latter replicated in culture with a doubling time of 40-60 h. They were initially fusiform; upon reaching monolayer confluency, they accumulated lipid and became rounder. Skin fibroblasts from the same patients and grown under the same culture conditions remained fusiform and did not accumulate lipid. The stromal-vascular fraction cells of adipose tissue may be fibroblasts with the potential to become adipocyte precursors. Subcellular preparations of the cells grown from the stromal-vascular fraction revealed lipoprotein lipase activity (characterized by such properties as inhibition by 1 M NaCl) that was not detectable in skin fibroblasts. The overall specific activity of the enzymes that catalyze triglyceride synthesis was 15 times higher and that of fatty acid synthetase was 2 times higher in the cells cultured from the stromal-vascular fraction. The difference was significant in each case. Conversely, when isolated mature adipocytes were cultured, they lost considerable lipid and acquired morphological characteristics similar to those of stromal-vascular fraction cells. Thus, adipose tissue stromal-vascular fraction cells acquire in culture many of the morphological and enzymological characteristics of mature fat cells.